A Morphometric Analysis of Nucleoli in Cultured Carcinoma Cells of the Human Thyroid. (1998) - Andersen, Lars; Kayser, Lars; Keiding, Niels; Thomsen, Jens
Abstract : Cells from 7 patients operated on for thyroid cancer were investigated. Samples of cells from the carcinoma and from the normal thyroid tissue were cultured with and without TSH stimulation. For light microscopy, serial sections of cells were cut and the size of nucleoli was measured and the number of nucleoli per cell counted. At the electron microscopic level the number and the volume of the fibrillar centres (FC) were estimated taking the Swiss cheese effect into account. The areal densities of FC, the fibrillar and granular component in nucleoli were determined by point counting. The results indicate that the malignant transformation has no influence on the size of the FC, but the observed numbers as well as the total area of FC are larger in cancer cells than in the normal thyroid epithelial cells. The nucleolar density of the fibrillar component is larger and that of the granular component is smaller in thyroid carcinoma cells than in non‐malignant thyroid epithelial cells ( p = 0.0001). Thus simple morphometry at the electron microscopic level might be helpful to discriminate between thyroid epithelial cells and thyroid carcinoma cells in culture.